2014
DOI: 10.1667/rr13578.1
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of the Synthetic Triterpenoid RTA 408 Protects Mice from Radiation-Induced Dermatitis

Abstract: Free radicals produced during cancer radiotherapy often leads to dermatitis, with the insult ranging from mild erythema to moist desquamation and ulceration. This toxicity can be dose limiting and promote chronic complications, such as fibrosis and wound recurrence. The purpose of this study was to evaluate if RTA 408, a synthetic triterpenoid that potently activates the antioxidative transcription factor Nrf2 and inhibits the proinflammatory transcription factor nuclear factor-kappa b (NF-κB), could protect s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 40 publications
(32 reference statements)
0
57
0
Order By: Relevance
“…Nrf-2 activation by the CDDO derivatives CDDO-ethylamide (EA) and CDDO-ME has been proposed to improve survival of irradiated mice (44). We observed that topical application of RTA 408 markedly reduced radiation dermatitis in mice associated with significant increases in Nrf2 target genes and significant decreases in NF-kB target genes (45). Interestingly, radiation protection of normal prostate epithelial cells contrasted by growth inhibition of prostate cancer cells in vivo has been very recently described for dimethylamineparthenolide (DMAPT) (46).…”
Section: Resultsmentioning
confidence: 99%
“…Nrf-2 activation by the CDDO derivatives CDDO-ethylamide (EA) and CDDO-ME has been proposed to improve survival of irradiated mice (44). We observed that topical application of RTA 408 markedly reduced radiation dermatitis in mice associated with significant increases in Nrf2 target genes and significant decreases in NF-kB target genes (45). Interestingly, radiation protection of normal prostate epithelial cells contrasted by growth inhibition of prostate cancer cells in vivo has been very recently described for dimethylamineparthenolide (DMAPT) (46).…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have been reported to inhibit inflammatory mediators, induce cell differentiation and induce apoptosis of cancer cells in vitro and also to be effective in many pathological models (Liby and Sporn, ). In addition, one of the CDDO scaffolds, RTA 408, is currently being tested in clinical trials for the treatment of, for example, radiation‐induced dermatitis (http://ClinicalTrials.gov identifier: NCT02142959) (Reisman et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Starting on day 2 and every second day thereafter, animals were scored in a blinded manner for ear thickness and dermatitis. Dermatitis scoring of all animals was performed analog to the Cancer Therapy Evaluation Program scale (31, 32). Briefly, dermatitis scoring ranged from: 0 = normal, no changes; 1 = mild erythema; 2 = moderate to severe erythema, slight desquamation; 3 = desquamation of 25–50% of irradiated area; 4 = desquamation of >50% of irradiated area; to 5 = frank ulcer.…”
Section: Methodsmentioning
confidence: 99%